The Impact of Market Power and Financial Flexibility on Corporate Investment Policy - Philip T. Fliers (Queen's University Belfast, Queen's Business School, 2024)
This study explores how market power and financial flexibility shape corporate investment policies among U.S. large and mature corporations, by estimating firm-specific, time-varying investment-to-added-value sensitivities. We find that firms with market power exhibit lower investment sensitivities, and this effect is more pronounced for the most financially flexible firms. We show that the firm's debt capacity is an important moderator in the relationship between market power and investment sensitivities. Our findings support theoretical predictions that market power and financial flexibility jointly influence investment decisions. The implication is that a lack of competition impedes corporate investments. For investors, these findings highlight the need to monitor both the competitive landscape and financial flexibility of firms in their portfolios.
Keywords: D40; G31; G32; 330; Investments; market power; financial flexibility; added-value; debt capacity